Motivation of Class XI Students towards Learning Physical Education Sports and Health - Yozi Kurniawan (Multidisciplinary Journal of Tourism, Hospitality, Sport and Physical Education, 2024)
Purpose of the study: This study aims to determine the level of motivation of class XI students towards learning physical education, sports and health at Public High School 2 South Bengkulu. Methodology: This research is a quantitative research, the method used is descriptive method with the type of survey. The population in this study were students of class XI Public High School 2 South Bengkulu, totaling 30 students. The sampling technique used was total sampling technique. The instrument used in this study used a Likert scale or questionnaire method which was distributed to respondents. Main Findings: Based on the results of the research on the motivation of Class XI students towards learning physical education, sports and health are classified as low, this can be seen in the results of the percentage of 87% which is in the assessment range of 81% -100% with very high criteria. Novelty/Originality of this study: This research provides a valuable contribution to further understanding of how motivation can be triggered and maintained at a high level among level XI students, particularly in the increasingly complex and diverse learning context of Physical Education, Sports and Health.